The Geology of Minneopa State Park - Thiel, George A. (Minnesota Department of Natural Resources, 1949)
Brief summary of the geology of Minneopa State Park, near Mankato, Minnesota.
One of a series of articles that appeared between 1947 and 1961 written by staff of the Minnesota Geological Survey and the University of Minnesota.
Keywords: geology; state park; Minnesota; Minneopa Creek